An entropy-based metric for assessing the purity of single cell populations - Baolin Liu; Chenwei Li; Ziyi Li; Dongfang Wang; Xianwen Ren; Zemin Zhang (Nature Communications, 2020)
Single cell RNA-seq is a powerful method to assign cell identity, but the purity of cell clusters arising from this data is not clear. Here the authors present an entropy-based statistic called ROGUE to quantify the purity of cell clusters, and identify subtypes within clusters.